Structure of the ichthyofauna of adventitious streams in the South Pantanal - Uieda, Virginia S. [UNESP]; Fujihara, César Y. (FapUNIFESP (SciELO), 2018)
The ichthyofauna of the Taquari River, one of the main tributaries of the South Pantanal, has been studied since the 1970s; however, there is a gap on the studies about the ichthyofauna present on the small adventitious streams of this highly dendritic system. These streams are small tributaries that flow directly into large rivers (mainstem), at least three orders greater in magnitude. The aim of this study was to analyze the structure of the ichthyofauna of five adventitious streams of the Upper Taquari River, South Pantanal, evaluating its temporal variation (dry and wet season) and the relation to the habitat characteristics and the conservation of the streams. Thirty-seven species were collected, from which 14 are exclusive to the Paraguay River basin, one species [Apteronotus albifrons (Linnaeus, 1766)] could represent a new record for this basin, and six species need taxonomic confirmation. The analysis indicated only the existence of spatial variation in the ichthyofauna structure of the streams sampled, with the similarity patterns related to the distance between the streams and to their conditions of conservation. The stream with greater size and preserved riparian forest was the one with the highest values of fish diversity and evenness. On the other hand, the stream with the smallest percentage of riparian forest and highest proximity to urban area presented the lowest diversity. The small size of these adventitious systems should serve as protection against large predators, which have their access to those areas hampered by their own size. Otherwise, the mainstem may also act as source of dispersal of small-bodied schooling fishes to the adventitious streams, where the greater heterogeneity of habitats and the presence of riparian vegetation should offer shelter and food supply for small species.
Estrutura da ictiofauna de riachos adventícios do Pantanal Sul
Keywords: Diversity; Fish; Lotic habitat; Paraguay River basin; Upper Taquari River